Assessing the potential of green CdO2 nano-catalyst for the synthesis of biodiesel using non-edible seed oil of Malabar Ebony. (1st February 2023) - Arshad, Sumera; Ahmad, Mushtaq; Munir, Mamoona; Sultana, Shazia; Zafar, Muhammad; Dawood, Sumreen; Rozina; Alghamdi, Ahmad M.; Asif, Saira; Bokhari, Awais; Mubashir, Muhammad; Chuah, Lai Fatt; et al.
Graphical abstract: Highlights: Diospyros malabarica is a novel feedstock for the synthesis of biodiesel. Biosynthesis of green CdO2 nanoparticles using Buxus papillosa leaf extract. Maximum yield of methyl ester 94 wt% was achieved under dynamic conditions. Biodiesel was produced by a single-step transesterification reaction. Green nanoparticles exhibit high stability, activity and cost effectiveness. Abstract: Sustainable biodiesel synthesis from waste, toxic and non-edible oil seeds give a sustainable opportunity to combat energy crises and environmental depreciation. A new non-edible oil of  Diospyros malabarica  (Malabar Ebony) was analyzed for the synthesis of eco-friendly biodiesel using newly synthesized green nanoparticles (NPs) of Cadmium oxide (CdO2 ) prepared from leaf extract of Buxus papillosa  via biological method followed by in situ wet impregnation approach. The highest fatty acid methyl ester (FAME) yield of 94 wt% was attained through the process of transesterification at ideal experimental conditions i.e., 1:9 M ratio of oil to methanol, catalyst loading 0.5 wt%, experiment duration 180 min and reaction temperature of 90 °C. Optimize biodiesel yield from Diospyros malabarica using response surface methodology was also applied. Scanning electron microscopy (SEM), energy dispersive X-ray (EDX), thermogravimetric analysis and X-ray diffraction (XRD) were utilized for the characterization of newly synthesized CdO2 NPs. The findings obtained from SEM revealed that CdO2 NPs were cubic in shape. The size of CdO2 NPs was 45 nm, which obtained from XRD analysis. EDX analysis showed 83.72 % cadmium composition. In thermogravimetric analysis, 5.2 % thermal degradation was observed which revealed that CdO2 NPs have strong thermal stability. The production of FAME was confirmed by using gas chromatography-mass spectroscopy (GC–MS), nuclear magnetic resonanceand Fourier transform infrared spectroscopy techniques. 9-Octadecenoic acid is the key fatty acid with the highest abundance in the GC–MS spectrum. This study revealed that inedible oil seed of Diospyros malabarica  and newly synthesized green NPs of CdO2 has the highest potential to be used as highly reliable cost-effective and sustainable entrants for synthesizing eco-friendly diesel which is ultimately open up the avenue for further research in the exploration and application of economical feedstock for biodiesel industry at a larger scale.